2010
DOI: 10.1093/humrep/deq343
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of early spontaneous abortions among Japanese: a matched case-control study

Abstract: Our finding suggests that for Japanese women, smoking and working may be important public health issue targets for the prevention of early spontaneous abortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 26 publications
1
34
1
2
Order By: Relevance
“…pollutants) and miscarriage risk (Green et al 2009;Sunil 2011). Lastly, substance abuse (cigarette, alcohol, drugs) has been associated with increased miscarriage risk (Baba et al 2011;Venners et al 2004;Oats and Abraham 1995;Lerner 2003) While close to 70 percent of all miscarriages happen before the 12 th week of pregnancy, the timing of miscarriage varies (see Figure 1.A). Cytogenetic analysis studies have shown that chromosomal abnormalities can cause spontaneous miscarriage at a range of gestational ages accounting for over 50 percent of all pregnancies lost before week 12 (with the peak prevalence at weeks 10-11) and over 35 percent of all pregnancies lost after week 12 (Kajii et al 1980;Eiben et al 1990;Hogge et al 2003;Philipp et al 2003 Our identification strategy relies on the assumption that miscarriages are correlated with the friend's childbearing status and uncorrelated with unobservable characteristics of the woman.…”
Section: Miscarriage As a Natural Experimentsmentioning
confidence: 99%
“…pollutants) and miscarriage risk (Green et al 2009;Sunil 2011). Lastly, substance abuse (cigarette, alcohol, drugs) has been associated with increased miscarriage risk (Baba et al 2011;Venners et al 2004;Oats and Abraham 1995;Lerner 2003) While close to 70 percent of all miscarriages happen before the 12 th week of pregnancy, the timing of miscarriage varies (see Figure 1.A). Cytogenetic analysis studies have shown that chromosomal abnormalities can cause spontaneous miscarriage at a range of gestational ages accounting for over 50 percent of all pregnancies lost before week 12 (with the peak prevalence at weeks 10-11) and over 35 percent of all pregnancies lost after week 12 (Kajii et al 1980;Eiben et al 1990;Hogge et al 2003;Philipp et al 2003 Our identification strategy relies on the assumption that miscarriages are correlated with the friend's childbearing status and uncorrelated with unobservable characteristics of the woman.…”
Section: Miscarriage As a Natural Experimentsmentioning
confidence: 99%
“…Such socioeconomic factors played an influential part in the health and life expectancies of the pregnancy and impact on pregnant outcomes, for people in low SES are more likely to show risky behavioral patterns and enjoy limited access to health services [10, 11]. A great number of, even as many as abundant, studies have well established the association among SES, onset of non-communicable diseases and cancer [12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 80% of miscarriages occur in the first trimester and the risk factors for the progression of a normal pregnancy to a complete miscarriage in the first trimester are properly well established [2]. Common risk factors include genetic anomalies, maternal age (35 years or older), high prepregnancy body mass index, history of previous miscarriage or ectopic pregnancy, and cardiovascular diseases [3].…”
Section: Introductionmentioning
confidence: 99%